Mejoramiento de procesos de planeación para la ejecución de obras privadas en la empresa Mera Peña (2021)
In the search for the identification and application of planning tools in private construction, it is evident that when it focuses on small companies, as is the case of the MERA PEÑA society, where, for the purposes of this Project, the planning process is reviewed of the HACIENDA JOSE MARIA project executed between February 2015 and May 2018. The MERA PEÑA Society has extensive experience in the construction market for strata 3, 4 and 5, however, through this study, the lack of a planning system that is applied from the beginning of the project is detected. the works, seeking to comply with what was proposed. in terms of Time, Scope and Costs, according to the project baseline. This degree work aims to identify and diagnose the causes of impact on the baseline of the project under review, and the determination and application of tools at the managerial level in planning for the improvement of processes in MERA PEÑA society.